Indoor Agriculture: Measurement of The Intensity of LED for Optimum Photosynthetic Recovery - Benediktus Anindito; Adri Gabriel Sooai; Mochammad Mizanul Achlaq; Moh Noor Al-Azam; Aris Winaya; Maftuchah Maftuchah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Indoor agriculture has begun in urban areas. With the narrowness of land and the model of vertical house development, makes this method of indoor agriculture has become a trend in several big cities in the world. Meanwhile, the one that is always needed by every plant is photosynthesis, and every natural photosynthesis of plants continually requires abiotic components of visible light from sunlight. That's why the indoor agriculture requires a replacement source of the sun with artificial sunlight. We can make this artificial sunlight from several light sources, such as incandescent lamps, compact fluorescent lamps (CFL), or the latest with Light Emitting Diode (LED). In this paper, we measured the intensity of light generated from several LEDs with some radiation distance to obtain the optimal energy for plants photosynthesis.